ANALYSIS PENGARUH AUGMENTED REALITY TERHADAP MINAT BELI MELALUI SPATIAL PRESENCE DAN PERCEIVED PERSONALIZATION (STUDI PRODUK KOSMETIK PADA APLIKASI JD.ID) - Temi Delizar Hudoyo (2022)
With the addition of 40 million new internet users in Southeast Asia during 2020 (400 million users in 2020 vs 360 million in 2019), referring to the e-Conomy Sea report data, 2020, has driven e-commerce GMV from 38 Billion USD in 2019 to 62 Billion USD in 2020, or grew by 63%. In Indonesia alone, e-commerce growth in this period was 54% (21 billion USD to 32 billion USD) and is estimated to reach USD 82 billion by 2025. The education, daily necessities, and online lending sectors received the highest growth in terms of early digital users, both through online media and e-commerce. Beauty products are one of the four main categories for e-commerce, this shows great potential for cosmetic products to penetrate e-commerce. According to data from the 2020 ZAP Beauty Index, purchasing beauty products through physical outlets is still the main choice. The main problems in buying beauty products are perception problems, including invalid or confusing information, color and size differences between online and real products, not being able to try the product in person, and not being able to find the desired color when shopping online. This study examines the use of AR in the beauty industry, supported by mobile technology, which can stimulate and provide benefits to the user experience.